Sources of PM2.5-bound water soluble ions at EMEP's Auchencorth Moss (UK) supersite revealed by 3D-Concentration Weighted Trajectory (CWT) model. (July 2021) - Dimitriou, Konstantinos; Mihalopoulos, Nikolaos; Leeson, Sarah R.; Twigg, Marsailidh M.
Abstract: The Concentration Weighted Trajectory (CWT) model is a well-known tool which combines the residence time (trajectory points) of air masses over specific regions with ambient concentrations of air pollutants, aiming to identify potential long range transport impacts. An upgraded 3D-version of CWT model (3D-CWT), investigating not only the geographical origin of the exogenous emissions but also the altitudinal layers in which the transport occurs, was developed and coupled with PM2.5 -bound concentrations of water soluble ions (nss- SO 4 − 2 (non-sea salt sulfates), NO 3 −, Cl −, NH 4 +, Na +, Mg + 2, Ca + 2 and K + ) for the years 2017–2018, derived by the Auchencorth Moss supersite in Southeast Scotland, United Kingdom (UK). The 3D-CWT model was implemented in two distinct altitudinal layers above ground level (0 m ≤ Layer 1 < 1000 m, 1000 m ≤ Layer 2 < 2000 m), because few trajectory points exceeded the 2000 m limit. Transport of Secondary Inorganic Aerosols (SIA) from South – Southeast England were detected in both vertical layers, affecting SO 4 − 2, NO 3 −, and NH 4 + levels, whilst SIA intrusions from Northwest Europe were detected in Layer 2. Sea salt particle transport from North Atlantic and the North Sea, comprising Cl −, Na + and Mg + 2, were detected in both layers whilst K + contributions from Southeast England were also detected in both layers, suggesting also impacts from biomass burning. Moreover particle transport of a crustal origin, marked by Ca + 2 enhancement, mainly occurred in layer 1 and included soil/dust resuspension from areas around the station and infrequent dust intrusions from the Sahara desert. Graphical abstract: Image 1 Highlights: Advanced 3D-CWT model was applied in Auchencorth Moss (UK) rural sampling site. PM2.5 -bound sea salt particles originated from North Atlantic and the North Sea. Intrusions of SIA from Southern England and Northwest Europe were indicated. Biomass burning aerosols from Southern England affected Auchencorth Moss. Regional soil resuspension and Saharan dust plumes enhanced crustal PM2.5 loadings.